2021
DOI: 10.1177/10497323211001344
|View full text |Cite
|
Sign up to set email alerts
|

Engagement With the Plan of Care Among Older Adults With Multiple Cardiac Diagnoses

Abstract: Aging adults depend on complex treatment plans to manage chronic conditions, yet little is known about their ability to perform the sophisticated behaviors required of technologically engaged patients. This qualitative descriptive study describes engagement with the plan of care. Forty chronically ill adults participated in this study, which involved an observation of the clinical encounter and an interview. Data were collected and analyzed simultaneously in keeping with principles of qualitative research. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Clorafi 24 showed that there are numerous initiatives underway to use health information technology to support patient engagement. However, the use of health information technology and other factors such as health literacy may be significant barriers to actually engage older adults.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clorafi 24 showed that there are numerous initiatives underway to use health information technology to support patient engagement. However, the use of health information technology and other factors such as health literacy may be significant barriers to actually engage older adults.…”
Section: Resultsmentioning
confidence: 99%
“…The literature reveals some important insights as concerns specific age groups. For example, Clorafi 24 showed that older adults need to have a positive relationship with the provider meeting the patient’s needs, and the distribution of a meaningful summary at the end of the provider visit in order to have clear take-away messages. Menichetti et al 59 examined the design, development and optimization of a theoretically driven intervention program (PHEinAction) to increase patient engagement in older chronic populations, and showed that it is important to consider emotional, psychological, and behavioral processes to support patient engagement among older patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These same participants did not engage in the use of technology to manage their care, perhaps preferring human support. 25 …”
Section: Introductionmentioning
confidence: 99%
“…These same participants did not engage in the use of technology to manage their care, perhaps preferring human support. 25 HCPs also experience numerous challenges in caring for PwMs, often reporting limited time to interact with patients, create formal integrated care plans or conduct medication reviews, as well as feeling burdened by having to monitor patient data. 7,12,[26][27][28] There is frequently dissonance between what patients' desire and what HCPs typically can, or are willing to, provide in terms of support for managing conditions.…”
Section: Introduction Backgroundmentioning
confidence: 99%